Identifikasi Potensi Jalur Wisata Menggunakan Geographic Information System Di Desa Kareloe, Kabupaten Jeneponto - Rafika Hayati; Lista Bella Handika Effendi; Maryam Yusuf (Politeknik Bosowa, 2026)
This study aims to identify potential tourism routes using Geographic Information System in Kareloe Village, Bontoramba District, Jeneponto Regency. Kareloe Village has hilly landscapes, rural scenery, and waterfall potential that have not been systematically mapped as a basis for nature-based tourism development. This research applied a descriptive qualitative approach supported by spatial analysis using Geographic Information System. Data were collected through field observation, coordinate recording, interviews, and documentation study. The results show that four potential natural tourism sites were identified, namely Mount Karempuang Peak at an elevation of 667.31 meters above sea level, Mount Bulupengka at an elevation of 585.52 meters above sea level, Salamatara Waterfall at an elevation of 384.11 meters above sea level, and Balloboro Waterfall at an elevation of 147.96 meters above sea level. These sites offer various attractions, including hilly panoramas, trekking routes, rural landscapes, and waterfalls. However, the identified tourism potential still faces several challenges, particularly in terms of accessibility, supporting facilities, route markers, and destination management. This study indicates that Geographic Information System can be used as a supporting tool to provide preliminary spatial information on the location, elevation, and distribution of natural tourism potential as a basis for more directed tourism route planning Keywords: Geographic Information System, tourism mapping, Kareloe Village